THE ROLE OF INDONESIAN WOMEN FOR CONFLICT RESOLUTION ON QUR'ANIC INTERPRETATION - Atabik, Ahmad (PALASTREN: Jurnal Studi Gender, 2019)
This article examines the Qur’an conflict perspective and the role of Indonesian women in conflict resolution efforts on a rural, regional and international scale. The results of this study indicate that conflicts in the Qur'an are presented in the form of stories with conflicts. Conflict stories in Qur’an are such as the conflict between Abel and Qabil, conflict between the Prophet Joseph and his brothers and conflict between the Prophet Moses and a Qibthi. The Qur’an is also about conflict resolution in various scattered verses. In the current conflicts, women have a significant role and efforts to resolve them. Indonesian women activists play a big role in conflict resolution that leads to the peace process. On a rural scale, the example is like conflict resolution by women activists in Gadingan village, Sliyeg Subdistrict, Indramayu Regency. On a regional scale such as the conflict resolution of women activists in Maluku and the international scale of conflict resolution conducted by Yenny Wahid on conflicts in Rohingya Myanmar.